Cortical anatomy plasticity in cases of cervical spondylotic myelopathy associated with decompression surgery: A strobe-compliant study of structural magnetic resonance imaging. Issue 4 (29th January 2021) - Liu, Meng; Tan, Yongming; Zhang, Chenlei; He, Laichang
Abstract : Abstract: Using voxel-based morphometry (VBM), we studied cortical gray matter volume changes in patients with cervical spondylotic myelopathy (CSM) before and after cervical cord surgical decompression. We then discussed the structural damage mechanisms and the neural plasticity mechanisms involved in postsurgical CSM. Forty-five presurgical CSM patients, 41 of the same group followed-up 6 months after decompression surgery and 45 normal controls (NC) matched for age, sex and level of education underwent high-resolution 3-dimensional T1-weighted scans by 3.0 T MR. Then, VBM measurements were compared and cortical gray matter volume alterations were assessed among pre- or postsurgical CSM patients and NC, as well as correlations with clinical indexes by Pearson correlation. Compared with NC, presurgical CSM patients showed reduced gray matter volume in the left caudate nucleus and the right thalamus. After 6 months, postsurgical CSM patients had lower gray matter volume in the bilateral cerebellar posterior lobes but had higher gray matter volume in the brain-stem than did presurgical CSM patients. Postsurgical CSM patients had significantly lower gray matter volume in the left caudate nucleus but greater regional gray matter volume in the right inferior temporal gyrus, the right middle orbitofrontal cortex (OFC) and the bilateral lingual gyrus / precuneus /posterior cingulate cortex than did NC. Abnormal areas gray volume in presurgical CSM and postsurgical CSM patients showed no significant correlation with clinical data ( P  > .05). Myelopathy in the cervical cord may cause chronic cerebral structural damage before and after the decompression stage, markedly in outlier brain regions involving motor execution/control, vision processing and the default mode network and in areas associated with brain compensatory plasticity to reverse downstream spinal cord compression and respond to spinal cord surgical decompression.